16th Annual Land O'Lakes Bioanalytical Conference. (November 2015) - Burns, Erik C; Guthrie, Randall H; Fluhler, Eric N; Stubbs, R John; Bateman, Kevin; King, Lindsay; Moran, Jeffrey
This Land O'Lakes Conference is presented each year by the Division of Pharmacy Professional Development within the School of Pharmacy at the University of Wisconsin-Madison (USA). The purpose of this 3-day conference is to provide an educational forum to discuss issues and applications associated with the analysis of xenobiotics, metabolites, biologics and biomarkers in biological matrices. The conference is designed to include and encourage an open exchange of scientific and methodological applications for bioanalysis. To increase the interactive nature of the conference, the program is a mixture of lectures, interactive discussions and a poster session. This report summarized the presentations at the 16th Annual Conference. 6th Annual Land O'Lakes Bioanalytical Conference, Fluno Center Madison, WI, USA, 13–16 July 2015